2019
DOI: 10.1063/1.5110475
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation-based color magnetic particle imaging for viscosity mapping

Abstract: Magnetic particle imaging (MPI) uses superparamagnetic iron oxide (SPIO) nanoparticles as biomedical imaging tracers. The potential applications of MPI have recently been broadened by the introduction of "color" MPI techniques that can distinguish different nanoparticles and/or environments, e.g., by exploiting the relaxation behavior of SPIOs. One of the important applications of color MPI techniques is viscosity mapping. In this work, we show relaxation-based color MPI experiments that can distinguish the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Since MPI has been validated in many stem cell therapy studies [ 33 , 34 , 35 , 36 , 37 ], we anticipate MPI’s advantages to be applicable to the adoptive cell therapy application as well. The main benefits of MPI in stem cells are innately transferable to the adoptive cell therapy application, such as (1) no loss in signal over time from magnetic cell labels enabling >90% of signal left over 89 days in vivo [ 33 ], (2) no radiation dose that will limit the length of a longitudinal study, (3) direct and quantitative measurement of magnetic label that is unaffected by changes in subject anatomy background over time [ 34 ], and (4) potential for assessment of viability of labeled cells via color MPI spectroscopic techniques demonstrated in various MPI studies that leverages microenvironment sensitivity for color/contrast change or for multi-contrast multiplexing [ 38 , 39 , 40 , 41 ]. These initial stem cell studies have demonstrated that the magnetic label remains internalized within the cell population of interest, and that any released label is rapidly cleared to the liver and does not confound the quantitation [ 33 ].…”
Section: Imaging Cancer Using Magnetic Particle Imagingmentioning
confidence: 99%
“…Since MPI has been validated in many stem cell therapy studies [ 33 , 34 , 35 , 36 , 37 ], we anticipate MPI’s advantages to be applicable to the adoptive cell therapy application as well. The main benefits of MPI in stem cells are innately transferable to the adoptive cell therapy application, such as (1) no loss in signal over time from magnetic cell labels enabling >90% of signal left over 89 days in vivo [ 33 ], (2) no radiation dose that will limit the length of a longitudinal study, (3) direct and quantitative measurement of magnetic label that is unaffected by changes in subject anatomy background over time [ 34 ], and (4) potential for assessment of viability of labeled cells via color MPI spectroscopic techniques demonstrated in various MPI studies that leverages microenvironment sensitivity for color/contrast change or for multi-contrast multiplexing [ 38 , 39 , 40 , 41 ]. These initial stem cell studies have demonstrated that the magnetic label remains internalized within the cell population of interest, and that any released label is rapidly cleared to the liver and does not confound the quantitation [ 33 ].…”
Section: Imaging Cancer Using Magnetic Particle Imagingmentioning
confidence: 99%
“…A new area of research has been focused on discerning multiple sources of iron based on core size, or viscosity and temperature of the medium ( 67 , 68 ), owing to differences in Brownian relaxation rates. It has been shown that 2 different SPIONs can be discerned in the same image ( 69 ), and this has promising implications to track and distinguish multiple cell types in cell tracking experiments ( 62 ).…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…Ultimately this background signal may obscure detection of cells, especially in low cell numbers 24 , as it is challenging (at this time, impossible) to distinguish the signal associated with cells from background. Second, there is some evidence that Brownian relaxation of SPION in different tissue environments may be altered, leading to reduced MPI sensitivity [25][26][27] . Brownian motion refers to the physical rotation of SPIONs; this motion is reduced in tissues with increased stiffness (e.g.…”
Section: Discussionmentioning
confidence: 99%